EEG complexity during mind wandering: A multiscale entropy investigation. (10th February 2023) - Cnudde, Kelsey; Kim, Gahyun; Murch, W. Spencer; Handy, Todd C.; Protzner, Andrea B.; Kam, Julia W.Y.
Abstract: Our attention often drifts away from the ongoing task to task-unrelated thoughts, a phenomenon commonly referred to as mind wandering. Ample studies dedicated to delineating its electrophysiological correlates have revealed distinct event-related potentials (ERP) and spectral patterns associated with mind wandering. It remains less clear whether the complexity of the electroencephalography (EEG) changes when our minds wander, a metric that captures the predictability of the time series at varying timescales. Accordingly, this study investigated whether mind wandering impacts EEG signal complexity. We further explored whether such effects differ across timescales, and change in a context-dependent manner as indexed by global and local levels of processing. To address this, we recorded participants' EEG while they completed Navon's global and local processing task and occasionally reported whether they were on-task or mind wandering throughout the task. We found that brain signal complexity as indexed by multiscale entropy decreased at medium timescales in centro-parietal regions and increased at coarse timescales in anterior and posterior regions during mind wandering, as compared to the on-task state, for global processing. Moreover, global processing showed increased complexity at fine to medium timescales compared to local processing. Finally, behavioral performance revealed a context-dependent effect in accuracy measures, with mind wandering showing lower accuracy compared to the on-task state only during the local condition. Taken together, these results indicate that changes in brain signal complexity across timescales may be an important feature of mind wandering. Highlights: Signal complexity captures flexibility in the dynamic functioning of the brain. We examined how mind wandering (MW) versus on-task states impact brain complexity. Complexity was greater at coarse timescales during MW compared to on-task periods. This suggests greater processing flexibility across functional configurations. Our findings indicate MW modulates the ongoing dynamic properties of the brain.